The Evolution of Digital Building Logbook: Exploring Building Information Gathering Systems to Boost Building Maintenance and Renovation - Martina Signorini; Mario Claudio Dejaco; Sonia Lupica Spagnolo (Applied Sciences)
The architecture, engineering, construction, and operations industry is distinguished by having plenty of and a variety of data, which makes the acquisition, storage, retrieval, and use of information difficult. Due to a data exchange system primarily based on paper-based transmission, multiple classification systems, the use of inconsistent criteria and practices, and a significant number of stakeholders involved during the building life cycle (each with distinct requirements and levels of access to information), the entire construction process must deal with ineffective information exchange among actors. Instead of multiple sources of information and tools to collect, store, and share data, one single source of information could become a reference point for numerous stakeholders. In this regard, a digital building logbook is assumed to be a collector of building-related data starting from the design phase, which plays a fundamental role in information management. This paper proposes a systematic literature review aimed at identifying the main features of the tool, investigating its growth in the construction sector. The results show that the digital building logbook’s main application is in the operations and maintenance field with relevance to renovation. However, a common model is absent, varying greatly based on the country and category of building. This analysis contributes to increasing awareness by identifying the attributes, gaps, and potentialities of the subject matter.